PENGARUH METODE BABY LED WEANING (BLW) TERHADAP POLA MAKAN ANAK USIA 9 - 12 BULAN DALAM UPAYA MENINGKATKAN STATUS GIZI ANAK DI DESA GADING WETAN KECAMATAN GADING KABUPATEN PROBOLINGGO - Iis Hanifah; Tutik Hidayati; Wahida Yuliana (Rena Cipta Mandiri, 2025)
One indicator of health development achievement is the nutritional status of children under 5 years old (toddlers). This phase is known as the golden period where development and growth are very rapid, so children's nutritional needs must be met. During this period, toddlers are very vulnerable to malnutrition, one of which is stunting. Although in East Java the figures have shown a decline in stunting, this is still not said to be completely successful because in Indonesia the target is to reach a stunting prevalence rate of 14% in 2024. The purpose of this study To determine the effectiveness of the baby-led weaning method on the eating patterns of children aged 9-12 months in an effort to improve children's nutritional status The method used in this study was a quasi-experiment with one group pretest posttest. The intervention was a technique of feeding babies aged 9-12 months using the baby-led weaning (BLW) method. The population in this study were all babies aged 9-12 months totaling 46 respondents. The sampling technique used a total sampling of 46 respondents. Data collection used a questionnaire, and was analyzed using the Wilcoxon statistical test. The results of this study indicate that Ha is accepted with an SPSS value of 0.001, which is <0.05, meaning that there is an Effect of the Baby Led Weaning (BLW) Method on the Eating Patterns of Children Aged 9 - 12 Months in an Effort to Improve Children's Nutritional Status. Suggestions, it is hoped that implementing the BLW method can help improve children's eating patterns and nutritional status. The output of this study is an accredited national journal.